Use of synbiotics in the production of fermented milk products - O. S. Chechenikhina; N. V. Leiberova; D. V. Dyldin; E. S. Smirnova; E. V. Razhina (Современная наука и инновации)
In the modern world, an increasing number of people are engaged in issues of proper nutrition in order to preserve their health. A promising direction for preserving the living status of the population is the creation of functional food products. Probiotics are given a special place in the production of functional food products. According to the World Health Organization, these components contribute to the suppression of pathogenic microorganisms and improve the functioning of the gastrointestinal tract. Probiotics include both bifidobacteria and lactobacilli present in fermented dairy products. The paper provides a justification for the optimal concentration of 0.5% and 0.8% of the symbiotic culture complex used in creating a recipe for thermostatic yogurt. The analysis of the resulting product showed its compliance with organoleptic and physico-chemical parameters.